Kepekatan Mn dan Fe dalam teras sedimen di Perairan Sarawak dan Sabah - Zal U'yun Wan Mahmood,; Zaharudin Ahmad,; Che Abd. Rahim Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Sediment cores were taken at eight stations along Sarawak and Sabah coastal waters using a gravity box corer on July 2004. The sediment cores were cut into 2 cm interval for measurement of Mn and Fe concentration using the Inductive Couple Plasma-Mass Spectrometer (ICP-MS). Overall, the sediment cores contained much mud which include a mixture of silt (46 – 67%) and clay (18 – 53%) compared to sand (0.4 – 16%). The concentrations of Mn and Fe were in the range of 154 – 366 μg/g and 0.9 – 3.4%, respectively. The variation was studied by ANOVA, which showed a significant difference (p = 0.000) for both of Mn and Fe concentrations at all sampling stations. In those ranges, Fe concentration was higher compared to Mn. It is believed that dissolving and diluting process influenced the concentration of Mn in the water column and sediment. Fe showed a significant correlation (r > 0.5, p < 0.01) with Mn at all stations except SR 03, indicating the natural occurrence of Mn and Fe in the water column. Meanwhile, Müller classification proved that sediment cores taken at 8 stations along Sarawak and Sabah coastal waters were not polluted with Fe and Mn with geoaccumulation index, Igeo < 1 and classification 0 – 1.